Política de saúde mental política de segurança: manicômio judiciário, entre o hospital psiquiátrico e a prisão - Costa, Maria Izabel Sanches (2009)
This dissertation aims to genealogically analyze the approach of legal and psychiatric discourses in defense of the insane criminal restraint in regard to security measure issues and they internment in Manicômios Judiciários (a Judiciary Mental Health Hospital), currently known as the Hospitals of Custody and Psychiatric Treatment (HCPT). Since the appearance of the psychiatrist in court, the figure of the insane criminal emerged as a freak that needs to be studied, treated and normalized. Thus, the knowledge of criminal psychiatry led health policies to approach the security policies as a way to suppress these dangerous individuals, removing them from the social living, legitimized by the concept of social dangerousness. Indeed, they were taken to the State custody, for the maintenance of order and the social welfare through the execution of the security measure. This work tried to investigate the technical procedures of power that produces a disciplinary control over the body, in regard to gestures, attitudes and behavior of insane criminals. From a study of the different historical phases of Manicômio Judiciário de Franco da Rocha, it was shown that the notion of dangerous individuals, and its proposal for the model of treatment / custody, changes in each current socio-political discourse